PENERAPAN PRINSIP POLLUTER PAYS PRINCIPLE DALAM PENCEMARAN MIKROPLASTIK: Implementation Of Polluter Pays Principle In Microplastic Pollution - Cena Lucia Uli; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2025)
This study discusses the application of the Polluter Pays Principle (PPP) in addressing microplastic pollution, which has a significant impact on the environment, human health, and the global economy. Microplastics, which originate from the incomplete decomposition of plastics, are widespread in soil, water, and air, and enter the human food chain. This raises the problem formulation in this article: What is the impact of microplastic pollution on the marine environment? How can the Polluter Pays Principle (PPP) regulate this pollution? The type of research used is a normative method with a descriptive approach, based on secondary data analysis in the form of primary, secondary, and tertiary legal materials. The PPP principle, as stipulated in the 1992 Rio Declaration and supported by various national and international regulations, requires polluters to be responsible for environmental recovery costs. The results of the study indicate that the implementation of the PPP can provide a deterrent effect for polluters and encourage the reduction of single-use plastics, innovation in environmentally friendly technologies, and funding for waste management. However, challenges such as the difficult-to-trace nature of microplastics and their global distribution require more intensive international cooperation and specific regulations.